BABY À LA CARTE - KULIKOVSKI, Victoria (BIBLIOPOLIS, 2020)
– Hello – Hello, here is the menu for you, I will come back in a minute for your order. Have you decided? – Yes, I would like a baby-boy, aristocratic white-skin, honeycomb colored eyes, light-burgundy cheeks and dark-cognac curly hair. His voices should have Pavarotti’s high notes and his intelligence should be equal to Aristotle’s. Personality- wise breaming with confidence and his physique oozing elegance.